Interactive Component in Oral Narratives of Preschool Children: on the Formulation of Hypothesis - Nadezhda Yurieva (Психолінгвістика)
The article presents an effort to elaborate the hypothesis for the experimental research devoted to interactive component in the oral narratives of preschool children. It is vital for psycholinguistics to reach a close approach to understanding of the essence of narrative processes which have in ontogenesis their own specifics, and according to some researches, these specifics are presented in indirect character of the process of narrative creation by child in the form of his verbal interaction with an adult.